Implementasi Sistem Hidrolik Pada Mesin Spandek Produksi di PT Primaland - Juniwan Juniwan; Endi Permata (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The purpose of this journal article is to provide research findings regarding the application of automated production control system theory to the construction industry. from expediting work processes. The method used in this research is to observe the production process of a Primalland light steel construction company in real time. Please note, raw materials can be obtained from literature studies, with a focus on their implementation in industrial processes. There are many challenges in the development sector in Indonesia, both in terms of quality and quantity, PT. PrimaLand Light Steel Frame was founded on December 25 2008 in Pandeglang. Based on the research that has been carried out, the data obtained from this research is then analyzed in detail to determine whether there is a significant difference between price changes that affect sales volume and price changes that affect sales volume. Research on sales volume at PT PrimaLand Pandeglang between 2014 - 2016. PrimaLand light steel tries as best as possible to maintain the quality of the roof truss profile produced by using high quality steel coils, or what can be called High Tension, namely with a yield strength range of Mega Pascal 400 Mpa – 500 Mpa and generally standard G550, or reaching 2x the strength from conventional melted steel which is more than 240 Mpa.